Redefining literary semiotics - Veivo, Harri; Ljungberg, Christina, 1949-; Johansen, Jørgen Dines (Cambridge Scholars, 2009)
This volume brings together cutting-edge essays on literary semiotics by well-known scholars in the field. In these clear, accessible essays, a broad range of central topics and approaches to literature are addressed to the most inclusive audience of lit.